2019
DOI: 10.1101/559245
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Human pathogen co-occurrence in Ixodes ricinus ticks: effects of landscape topography, climatic factors and microbiota interactions

Abstract: 5The factors shaping microbial communities within organisms are still poorly understood. Besides

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 99 publications
1
10
1
Order By: Relevance
“…In this longitudinal three-year study, two TBP associations were significantly overrepresented compared to a random distribution: the first one was between B. garinii and B. afzelii , as has been previously observed in studies using similar detection tools [22, 42], or different methods ( 16S rRNA gene sequencing [64]); the second one was between B. garinii and B. spielmanii . Interestingly, these findings contrast with published results on I. ricinus TBPs.…”
Section: Discussionsupporting
confidence: 67%
“…In this longitudinal three-year study, two TBP associations were significantly overrepresented compared to a random distribution: the first one was between B. garinii and B. afzelii , as has been previously observed in studies using similar detection tools [22, 42], or different methods ( 16S rRNA gene sequencing [64]); the second one was between B. garinii and B. spielmanii . Interestingly, these findings contrast with published results on I. ricinus TBPs.…”
Section: Discussionsupporting
confidence: 67%
“…A previous study on the microbiome of I. ricinus also observes an unstable microbial composition (Aivelo et al, 2019a(Aivelo et al, , 2019b. However, contrary to our findings, Aivelo et al found M. mitochondrii in all sequenced ticks (n = 82).…”
Section: Limited Microbiome Of Ixodes Ricinuscontrasting
confidence: 99%
“…and Francisella spp., and Lariskella spp. (Aivelo et al, 2019a(Aivelo et al, , 2019bSpitalska et al, 2018;Wojcik-Fatla et al, 2015). However, it is unknown what their functional role is and whether they are genuinely associated with this tick species.…”
mentioning
confidence: 99%
“…Which spatial scale is the best investigation of the tick microbiome? Field studies have shown the strong influence of biogeography at large scales (states or regions) on the tick microbiome structure and composition on different tick species, I. scapularis [66], I. ricinus [109][110][111] and A.…”
Section: Is the Spatial Scale Necessary To Efficiently Study The Tickmentioning
confidence: 99%